Radiosynthesis and evaluation of a novel monoacylglycerol lipase radiotracer: 1, 1, 1, 3, 3, 3-hexafluoropropan-2-yl-3-(1-benzyl-1H-pyrazol-3-yl)azetidine-1-[11C]carboxylate. Issue 16 (15th August 2019) - Mori, Wakana; Hatori, Akiko; Zhang, Yiding; Kurihara, Yusuke; Yamasaki, Tomoteru; Xie, Lin; Kumata, Katsushi; Hu, Kuan; Fujinaga, Masayuki; Zhang, Ming-Rong
Graphical abstract: Abstract: Monoacylglycerol lipase (MAGL) is a major serine hydrolase that hydrolyses 2-arachidonoylglycerol (2-AG) into arachidonic acid (AA) and glycerol in the brain. Because 2-AG and AA are endogenous biologically active ligands in the brain, the inhibition of MAGL is an attractive therapeutic target for neurodegenerative diseases. In this study, to visualize MAGL via positron emission tomography (PET), we report a new carbon-11-labeled radiotracer, namely 1, 1, 1, 3, 3, 3-hexafluoropropan-2-yl-3-(1-benzyl-1 H -pyrazol-3-yl)azetidine-1-[ 11 C]carboxylate ([ 11 C]6 ). Compound6 exhibited high in vitro binding affinity (IC50 = 0.41 nM) to MAGL in the brain with a suitable lipophilicity (cLogD = 3.29). [ 11 C]6 was synthesized by reacting 1, 1, 1, 3, 3, 3-hexafluoropropanol (7 ) with [ 11 C]phosgene ([ 11 C]COCl2 ), followed by a reaction with 3-(1-benzyl-1 H -pyrazol-3-yl)azetidine hydrochloride (8 ), which resulted in a 15.0 ± 6.8% radiochemical yield (decay-corrected, n = 7) based on [ 11 C]CO2 and a 45 min synthesis time from the end of bombardment. A biodistribution study in mice showed high uptake of radioactivity in MAGL-rich organs, including the lungs, heart, and kidneys. More than 90% of the total radioactivity was irreversibly bound in the brain homogenate of rats 5 min and 30 min after the radiotracer injection. PET summation images of rat brains showed high radioactivity in all brain regions. Pretreatment with6 or MAGL-selective inhibitor JW642 significantly reduced the uptake of radioactivity in the brain. [ 11 C]6 is a promising PET tracer which offers in vivo specific binding and selectivity for MAGL in rodent brains.